Characterization of Powdery Mildew Fungi Affecting Hemp in the Pacific Northwest - Hannah M. Rivedal; Michele S. Wiseman; Briana J. Richardson; Stephen T. Massie; Andrea R. Garfinkel; Cynthia M. Ocamb; David H. Gent (PhytoFrontiers, 2024)
Hemp (Cannabis sativa) is a new crop for Oregon and Washington. These states are also home to 90% of the country's hop (Humulus lupulus) production. Powdery mildew is a common disease that affects both hemp and hop. There are at least two species of powdery mildew fungi that may occur on hemp, including Golovinomyces ambrosiae and Podosphaera macularis, with the latter also infecting hop. Surveys were conducted throughout Oregon and Washington in 2021 and 2022 to determine the incidence and identity of powdery mildew fungi on hemp. Seventy-four fields were evaluated at three time points. In Oregon, powdery mildew was not detected in either year in the early season but was detected in 4.6 to 6.5% of fields during mid-season and 36.8 to 41.4% of fields during late-season evaluations. Powdery mildew was not detected in Washington in any survey time point in either year. We collected 204 powdery mildew samples from surveyed fields. Both P. macularis and G. ambrosiae were detected on hemp, based on diagnostic PCR assays and sequencing, comprising approximately 17 and 96% of assayed survey samples, respectively. All P. macularis samples that amplified were mating type MAT1-1, consistent with the population occurring on hop in the region. Thirty-nine convenience samples were collected outside of surveyed fields and included the first detections of both G. ambrosiae and P. macularis on hemp in Washington. The presence of P. macularis on hemp has possible ramifications for hop producers in the region, including disruption of established management systems and introduction of novel isolates. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2024.